Analisis Pendapatan Pedagang Kaki Lima Sektor Informal Di Kecamatan Rappocini Kota Makassar - Marhawati, Marhawati (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2020)
Street Vendors are one of the informal sectors that are found in urban areas. The existence of street vendors does not always require formal education and high skills and does not require a large capital. This study aims to determine the factors that affect the income of street vendors in Talasalapang Street, Rappocini Regency, Makassar City. The population in this study was not greater than 100 people, so the census technique was used by taking the overall population of 60 street vendors. The analysis technique used is Multiple Linear Regression using a partial hypothesis test (t-test) and simultaneous (F test), using SPSS 21. The results showed that capital, business experience, and time allocation of trying to jointly affect street vendors' income. Partially shows that capital and time allocation try to have a positive and significant effect on street vendors 'income, while the experience of trying not to affect street vendors' income on Talasalapang Street, Rappocini Regency, Makassar City